The influence of digital platform on the implementation of corporate social responsibility: from the perspective of environmental science development to explore its potential role in public health - Wang, Mansi; Yuan, Renmiao; Guan, Xin; Wang, Zeyu; Zeng, Yanzhao; Liu, Tao (Frontiers in Public Health, 2024)
This paper aims to explore the intersection of corporate social responsibility (CSR) and public health within the context of digital platforms. Specifically, the paper explores the impact of digital platforms on the sustainable development practices of enterprises, seeking to comprehend how these platforms influence the implementation of environmental protection policies, resource management, and social responsibility initiatives. To accomplish this objective, a questionnaire survey targeting employees in private enterprises is conducted. This paper finds that there is a significant positive correlation between the wide application of digital platform and the environmental protection behavior of enterprises ( r = 0.523; p < 0.001 ), and the innovative technology of environmental protection in the digital platform has a positive impact on the implementation of environmental protection policies ( a * b/c = 55.31% ). These statistics emphasize the potential of digital platforms in promoting corporate social responsibility and public health. The intermediary analysis indicates that environmental innovation technology plays a mediating role in the influence of digital platforms on the environmental behavior of enterprises. Furthermore, the adjustment analysis underscores that enterprises of varying scales and industries exhibit distinct responses to digital platforms. This insight is crucial when formulating environmental protection policies and strategies. By bridging the existing knowledge gap on the relationship between digital platforms and corporate environmental behavior, this paper contributes valuable insights for the integration of CSR principles into public health considerations. The paper provides practical and policy-oriented enlightenment, offering support for enterprises and governments in crafting more effective environmental policies and strategies to foster sustainable development goals.